How Consumer Trust Moderating Effect on Purchase Intention of Halal Food Product? - Nadia Audina; Nuryakin; Handayani, Siti Dyah (Archives of Business Research, 2022)
The purpose of this research is to analyze the effect of price perception and Halal label on purchase intention with consumer trust as a moderator on food private label at Super Indo retail stores. The population on this research are Super Indo’s consumers who understand about private label products. The data collection used questionnaire method. There are 223 respondents. The analytical tool used in this study is SEM (Stuctural Equation Modeling) which is operated with the AMOS ver.22 program. The findings show that: (1) Price perception has positive and significant effect on food private label purchase intention. (2) Halal label has positive and significant effect on food private label purchase intention. (3) Consumer trust as a moderator has a positive and significant effect on the relationship between price perception and purchase intention. (4) Furthermore, consumer trust as a moderator also has a positive and significant effect on relationship between Halal label and purchase intention. In addition, the factors that influence purchase intentions in the study only consist of price perception and Halal labels.